Synthesis and Antimicrobial Studies of Some 4-(Substituted)-Ethanoylamino-3-Mercapto-5- (4-Substituted) Phenyl-1,2,4-Triazoles - Upmanyu, Neeraj; Kumar, Sanjay; Shah, Kamal; Mishra, Pradeep (Dhaka University Journal of Pharmaceutical Sciences, 2012)
Triazoles and triazoles with different substituent groups are found to possess diverse application in the field of medicine and industry. A series of 4-(substituted) ethanoylamino-3-mercapto-5-(4-substituted) phenyl-1,2,4- triazoles were synthesized as novel antimicrobial agents starting from different 4-substituted benzoic acids. The chemical structures of these newly synthesized compounds were elucidated by IR, 1H NMR, 13C NMR, FAB+-mass spectral data and elemental analyses. The antimicrobial activity of title compounds were examined against two gram positive bacteria (Staphylococcus aureus, Bacillus subtilis), two gram negative bacteria (Escherichia coli, Pseudomonas aeruginosa) and three fungi (Candida albicans, Aspergillus niger and Fusarium oxysporum) using disc diffusion method. Some of the compounds bearing methoxy group exhibited moderate to good antibacterial and antifungal activities. DOI: http://dx.doi.org/10.3329/dujps.v11i1.12481 Dhaka Univ. J. Pharm. Sci. 11(1): 7-18, 2012 (June)